2019
DOI: 10.15181/ab.v26i0.2022
|View full text |Cite
|
Sign up to set email alerts
|

The Decorated Spindle-Shaped Bone Dagger from Šarnelė: the Earliest Example of Hunter-Gatherer Mobile Art in Lithuania

Abstract: This paper presents the latest data on a spindle-shaped decorated bone dagger, which was found as a stray find in the village of Šarnelė in northwest Lithuania, and which recently been dated to the Final Palaeolithic. It is currently the only one such example of osseous technology in Lithuania dated to this period. In 2016, we started to reinvestigate the Stone Age material from the Samogitian highland by AMS radiocarbon (14C) dating, stable isotopes, use-wear and Raman methods. AMS dating showed that the deco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…54 Unfortunately, the spindle-shaped bone point from Kalniškiai cannot be directly compared with the dated one from Šarnelė (north western Lithuania), which belongs to the end of the Youngers Dryas. 55 These two tools have different shapes and, most likely, had different functions. The exact parallel in tool shapes can be found in northern Lithuania, where spindleshaped bone point with narrow tang from Pumpėnai village has been found, although this find likewise has not been directly dated.…”
Section: Discussionmentioning
confidence: 99%
“…54 Unfortunately, the spindle-shaped bone point from Kalniškiai cannot be directly compared with the dated one from Šarnelė (north western Lithuania), which belongs to the end of the Youngers Dryas. 55 These two tools have different shapes and, most likely, had different functions. The exact parallel in tool shapes can be found in northern Lithuania, where spindleshaped bone point with narrow tang from Pumpėnai village has been found, although this find likewise has not been directly dated.…”
Section: Discussionmentioning
confidence: 99%
“…Dates were calibrated using OxCal v.4.4.4 (Bronk Ramsey 2017) and the IntCal20 atmospheric curve (Reimer et al 2020) and reported at 95.4% probability. For comparison, we also re-calibrated five previously published radiocarbon dates from two slotted (Ivanovaitė et al 2018) and three barbed points (Ivanovaitė et al 2018;Butrimas 2019), which dating was performed in Aarhus (AAR) and Brussels (RICH) AMS laboratories. The ATR-FTIR spectra of adhesive samples from six bone points are presented in Figure 6.…”
Section: Datingmentioning
confidence: 99%
“…The first radiocarbon dating of stray bone and antler harpoons from Lake Lubāns (Latvia) indicated the continuation of Final Paleolithic technology in the Early Holocene, informing discussion of the transition between the Final Paleolithic and the earliest Mesolithic (Meadows et al 2014). More chronological investigations of single osseous artifacts from the eastern Baltic followed, creating typo-chronological models for particular Late Pleistocene and Holocene organic implement technologies (Ivanovaitė et al 2018; Philippsen et al 2019; Zagorska et al 2019; Rimkus et al 2019; Piličiauskas et al 2020). These studies provided many important insights, involving such aspects as when the eastern Baltic region was settled at the end of the Late Glacial and how certain tool types developed in the Holocene.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research on this collection indicates that the artefacts belong to different periods. There is no doubt that human activity in the area began as early as the end of the Late Glacial and continued into the Mesolithic, while more finds are known from the Late Holocene period (Butrimas 2019;Rimkus et al 2019). One T-shaped antler axe was identified among stray finds.…”
Section: 5 Me L N R a G ė I Imentioning
confidence: 99%